The administration of methotrexate in patients with Still's disease, “real-life” findings from AIDA network still disease registry - DİRESKENELİ, RAFİ HANER (My University, 2023)
Objectives: To describe clinical characteristics of patients with Still\"s disease treated with methotrexate (MTX) and to assess drug effectiveness evaluating change in disease activity, reduction of inflammatory markers, and glucocorticoid (GC)-sparing effect. Methods: Patients with Still\"s disease treated with MTX were assessed among those included in AIDA Network Still Disease Registry. Results: In this registry, 171 patients with Still\"s disease were treated with MTX (males 43.3%, age 37.1 ± 16.0 years). They were mainly characterised by joint features and fever without a prominent multiorgan involvement. MTX was administered with GCs in 68.4% of patients, with other conventional synthetic DMARDs in 6.4%, and with biologic DMARDs in 25.1%. A significant reduction of the modified systemic score was observed, and 38.6% patients were codified as being in clinical remission at the end of follow-up. The concomitant administration of a biologic DMARD resulted a predictor of the clinical remission. Furthermore, a reduction of inflammatory markers and ferritin levels was observed following the administration of MTX. Additionally, a marked reduction of the dosage of concomitant GCs was identified, while 36.7% discontinued such drugs. Male gender appeared as a predictor of GC discontinuation. MTX was discontinued in 12.3% of patients because of adverse effects, and in 12.3% for lack of efficacy. Conclusions: Clinical characteristics of patients with Still\"s disease treated with MTX were described, mainly joint features and fever without a prominent multiorgan involvement. The clinical usefulness of MTX was reported in reducing the disease activity, decreasing the inflammatory markers, and as GC-sparing agent.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; ANESTHESIOLOGY; Romatoloji; Anesteziyoloji ve Ağrı Tıbbı; Rheumatology; Anesthesiology and Pain Medicine; Adult-onset still's disease; Methotrexate; Still's disease; Systemic juvenile idiopathic arthritis; Treatment